Transplant candidates' perceptions of informed consent for accepting deceased donor organs subjected to intervention research and for participating in posttransplant research. Issue 2 (23rd October 2019) - Gordon, Elisa J.; Knopf, Elizabeth; Phillips, Caitlin; Mussell, Adam; Lee, Jungwha; Veatch, Robert M.; Abt, Peter; Dunn, Sue; Reese, Peter P.
Abstract : Deceased donor organ intervention research holds promise for increasing the quantity and quality of organs for transplantation by minimizing organ injury and optimizing function. Such research will not progress until ethical, regulatory, and legal issues are resolved regarding whether and how to obtain informed consent from transplant candidates offered intervention organs given time constraints intrinsic to distribution. This multi‐center, mixed‐methods study involved semi‐structured interviews using open‐ and closed‐ended questions to assess waitlisted candidates' preferences for informed consent processes if offered an organ after undergoing intervention. Data were analyzed thematically. Sixty‐one candidates participated (47% participation rate). Most were male (57%), white (61%), with a mean age of 56 years. Most candidates (79%) desired being informed that the organ offered was an intervention organ before accepting it, and were likely to accept an intervention organ if organ quality was good (defined as donor age 30) (81%), but fewer candidates would accept an intervention organ if quality was moderate (ie, donor age 50) (26%). Most perceived informed consent important for decision‐making, while others considered it unnecessary given medical necessity to accept an organ and trust in their physician. Our findings suggest that most candidates desire an informed consent process before accepting an intervention organ and posttransplant data collection. Abstract : This study of waitlisted candidates' preferences for informed consent regarding organs that have been subjected to intervention research finds that most candidates desire providing informed consent before accepting an intervention organ and posttransplant data collection.